Recharge of chondrocyte mitochondria by sustained release of melatonin protects cartilage matrix homeostasis in osteoarthritis. Issue 2 (3rd July 2022) - Zhang, Yijian; Hou, Mingzhuang; Liu, Yang; Liu, Tao; Chen, Xi; Shi, Qin; Geng, Dechun; Yang, Huilin; He, Fan; Zhu, Xuesong
Abstract: Recent evidence indicates that the mitochondrial functions of chondrocytes are impaired in the pathogenesis of osteoarthritis (OA). Melatonin can attenuate cartilage degradation through its antioxidant functions. This study aims to investigate whether melatonin could rescue the impaired mitochondrial functions of OA chondrocytes and protect cartilage metabolism. OA chondrocytes showed a compromised matrix synthesis capacity associated with mitochondrial dysfunction and aberrant oxidative stress. In vitro treatments with melatonin promoted the expression of cartilage extracellular matrix (ECM) components, improved adenosine triphosphate production, and attenuated mitochondrial oxidative stress. Mechanistically, either silencing of SOD2 or inhibition of SIRT1 abolished the protective effects of melatonin on mitochondrial functions and ECM synthesis. To achieve a sustained release effect, a melatonin‐laden drug delivery system (DDS) was developed and intra‐articular injection with DDS successfully improved cartilage matrix degeneration in a posttraumatic rat OA model. These findings demonstrate that melatonin‐mediated recharge of mitochondria to rescue the mitochondrial functions of chondrocytes represents a promising therapeutic strategy to protect cartilage from OA.